United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Consolidated Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2010)
This note reviews outgoing U.S. consolidated regulatory and supervisory arrangements and explores options to strengthen them. Although U.S. consolidated regulation and supervision span from the smallest financial groups to the largest and most complex, much effort is focused on the latter. This note addresses the basic statutory arrangements for consolidated regulation and supervision, as distinct from the actual exercise. It is stressed that, of all the U.S. regulatory bodies, it is the Federal Reserve that is best placed to bear the consolidated supervisory mandate.